MEREFLEKSIKAN NILAI ISLAMI MELALUI PENGEMBANGAN METERI FISIKA DI ACEH - Zulkarnaini, Zulkarnaini; Faisal, Muhammad; Muzana, Syarifah Rahmiza; Lubis, Silvi Puspa Widya; Fatimah, Jannatun (Jurnal Dedikasi Pendidikan, 2024)
The aim of this research is to develop a Physics textbook at the upper secondary level that reflects the values of Islamic education. The development of this physics book is also enrichment material using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) approach model. In developing the learning materials, 5 physics teachers were involved for five high schools in Aceh Besar, where 10 students were taken per school for a total of 50 students. At the analysis stage, researchers use self-evaluation to ensure the feasibility of the analysis. Apart from that, prototype II was also developed in the form of several chapters involving one religious lecturer. Furthermore, these chapters were tested directly on all students to see the students' cognitive and behavioral mastery over the centuries and whether their attitudes reflected correct Islamic values and were in accordance with the religious demands of being a Muslim. The results of the research show that: (1) the development of Islamic-based physics material can build students' cognitive and affective domains which are characterized by good behavior and mutual respect, (2) Physics books with an Islamic character curriculum make students appear polite and confident, (3) Teachers as curriculum developers and implementers feel responsible for taking anticipatory steps so that physics books in schools can truly reflect Islamic values as a whole, both in terms of validity and practicality.